Small states, small problemsn - Easterly, William Russell (Policy research working paper, 1999)
Small states, no different from large states in income and growth, should receive the same policy advice large states do. Because of their greater openness, they may be more vulnerable to volatility in terms-of-trade shocks--but their openness pays off in growth.